EL MÉDANO ROCK PAINTING STYLE ON THE COAST OF THE ATACAMA DESERT IN CHILE: CETECEAN HUNTING OR CETACEAN AS SOCIAL AGENTS? - Dellepiane, José Castelleti (Revista Cuadernos de Arte Prehistorico, 2021)
Investigations carried out in recent decades in Paposo/Taltal (25°S, Atacama Desert coast) have contrasted the academic corpus pillars of the so-called El Médano rock painting style. This style interprets the local pictograph representations characterized by the design of marine animals and boats made with red pigment asdemonstration of physical cetacean hunting by coastal Indigenous people from 2000 years ago until Spanish/Indigenous contact moments, a behavior supposedly witnessed by the Spanish chronicler Vázquez de Espinosa in 1618. On the contrary,a reinterpretation of this traditional model, in view of the new data obtained for the archeology of Taltal, allows us to rule out physical hunting events of large cetaceans from prehistory in this coastal area, given the null presence of material indicators that attest both, technologically and as garbage disposal. The contrast between the ethnohistoric information present for the coast of Paposo/Taltal and new data on local archeology and specifically on the iconography and materiality of the Médano pictographs openup the possibility of new interpretations of the real interaction that human groups and cetaceans had in the local landscape construction since prehistory.